Le travail émotionnel à l’épreuve du cancer colorectal - Ludovic Gaussot; Nicolas Palierne; Estelle Laurent; Isabelle Ingrand (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article is questioning the various aspects of emotional work, professional and lay, which appear in experiences and familial risk of colorectal cancer. It relies on thematic analysis of thirty monographs of treated persons under 65, including their caregivers and their relatives at risk. While the emotional work attached to illness experience tends to assuage negative feelings, the preventive emotional work tends to assess them overtly. The efficiency of family prevention includes the adjustment of domestic emotional work between the sense of invulnerability and the anxious inhibition of the procedure to the colonoscopy. This work of adjustment questions the very nature of family relations, gender division of emotional and domestic works, not undermining age and social class.